T thefrog May 2010 20 0 May 24, 2010 #1 \(\displaystyle \nabla\cdot[v(x\cdotv)]=\nabla(\frac{1}{2}v^2x)-\frac{1}{2}v^2+v\cdot(x\timesw\)

D dwsmith MHF Hall of Honor Mar 2010 3,093 582 Florida May 24, 2010 #2 thefrog said: \(\displaystyle \nabla\cdot[v(x\cdotv)]=\nabla(\frac{1}{2}v^2x)-\frac{1}{2}v^2+v\cdot(x\timesw\) Click to expand... \(\displaystyle Latex error\to correct formatting\to help received\) (Bigsmile) Reactions: AllanCuz

thefrog said: \(\displaystyle \nabla\cdot[v(x\cdotv)]=\nabla(\frac{1}{2}v^2x)-\frac{1}{2}v^2+v\cdot(x\timesw\) Click to expand... \(\displaystyle Latex error\to correct formatting\to help received\) (Bigsmile)